The brain microenvironment: friend or foe for metastatic tumor cells? - Winkler, Frank (Neuro-Oncology, 2014)
Brain metastases continue to be challenging targets for therapy and prevention. One reason is that many chemotherapeutics that work well on systemic metastases
Gesehen am 13.10.2020